Trees and sidewalks: toward an infrastructure protection approach - Otero-Durán, Laura; Torres, Andrés (Frontiers in Sustainable Cities, 2024)
Among the global strategies to achieve urban resilience, nature-based solutions (NbS) emerge within the green infrastructure (GI) as a path to deal with climate change. This work aims to propose an approach to promote symbiosis between the green and gray infrastructure. It includes a review of guidelines and scientific papers for species selection, and the design of root containers. Also, a multicriteria and water comfort analysis for decision-making regarding species selection in specific city areas. We applied this methodology to one case study (Bogotá), but it can be used in any city with basic knowledge of the species suitable for planting in a built public space. We obtained a list of crucial criteria for selecting local species for sidewalks. Among these criteria, are those related to the size of the species, characteristics of permeability and soil compaction, and climatic conditions. We obtained a list of desirable species adapted to all the humidity zones of the case study city. The hydrological sizing methods proposed depend both on the species to be planted, and the geometry of the streets. The presented approach and findings promote the trees development and their ecosystem services, while preventing the damage to the surrounding infrastructure.